2005
DOI: 10.1111/j.0030-1299.2005.13794.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding patterns by roe deer and rabbits on pine, willow and birch in relation to spatial arrangement

Abstract: 2005. Feeding patterns by roe deer and rabbits on pine, willow and birch in relation to spatial arrangement. Á/ Oikos 109: 513 Á/520.The location of a plant and its association with the surrounding vegetation may be a strong determinant of herbivore foraging decisions. The attractiveness of a food plant may be reduced if associated with a less preferred one (repellent Á/plant hypothesis) or, conversely, it may escape herbivory via association with a more preferred species (attractant Á/decoy hypothesis). In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 34 publications
0
51
2
Order By: Relevance
“…The associational susceptibility of trees in high-quality neighborhoods can be explained if koalas also make foraging decisions at a larger ''patch'' scale resulting in a preference for ''good'' neighborhoods. Other studies have also shown that herbivores make simultaneous foraging decisions at multiple scales in experimental arenas (Hja¨lte´n et al 1993, Bergman et al 2005, but the success of this study in describing these processes in natural, continuous vegetation illustrates the value of this fine-scale mapping approach.…”
Section: Discussionmentioning
confidence: 67%
“…The associational susceptibility of trees in high-quality neighborhoods can be explained if koalas also make foraging decisions at a larger ''patch'' scale resulting in a preference for ''good'' neighborhoods. Other studies have also shown that herbivores make simultaneous foraging decisions at multiple scales in experimental arenas (Hja¨lte´n et al 1993, Bergman et al 2005, but the success of this study in describing these processes in natural, continuous vegetation illustrates the value of this fine-scale mapping approach.…”
Section: Discussionmentioning
confidence: 67%
“…Additionally, roe deer were reported to feed highly selectively (Bergman et al 2005;Moser et al 2008;Jarni et al 2004). Given that the selection of browsing sites can be explained by differences in the food quality (Jarni et al 2004), the different taste of Turkey oak and chestnut sprouts could accordingly likely contribute to the observed browsing pattern.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in Scandinavian forests aspen, pine and birch are more attractive to moose (Alces alces) than Norway spruce (Jalkanen 2001;Kullberg and Bergstrom 2001). However, not only specific preferences but also the surrounding landscape matrix will affect the probability of an individual seedling being browsed (Hornberg 2001;Edenius et al 2002;Bergman et al 2005). Browsing tends to be more intense in mixed species stands and, unsurprisingly, most severe in stands dominated by mixtures of attractive species (Vehviläinen and Koricheva 2006;Milligan and Koricheva 2013).…”
Section: Introductionmentioning
confidence: 99%